Developing and Applying a User-Centered Model for the Design and Implementation of Information Visualisation - KOH, Lian Chee (Institutional Knowledge at Singapore Management University, 2011)
The objective of this paper is to show how approaches for user-centered information visualization design and development are being applied in the context of healthcare where users are not familiar with information visualization techniques. We base our design methods on user-centered frameworks in which ‘prototyping’ plays an important role in the process. We modify existing approaches to involve prototyping at an early stage of the process as the problem domain is assessed. We believe this to be essential, as it increase users’ awareness of what information visualization techniques can offer them and that it enables users to participate more effectively in later stages of the design and development process. This also acts as a stimulus for engagement. The problem domain analysis stage of a pilot study using this approach is presented, in which techniques are being collaboratively developed with analysts from a healthcare institution. Our results suggest that this approach has engaged users, they are able apply more generic information visualization concepts to their domains and as a result are better equipped to take part in the subsequent collaborative design and development process.